Evaluating the Performance of Secondary Schools in the Gaza Strip in Light of the Balanced Scorecard and Its Relationship to Institutional Excellence: The Mediating Role of Organizational Commitment - Abu Borhom, Mohammed Ibrahim; Al-Muzain, Suleiman Hussein (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the degree of implementation of the Balanced Scorecard (BSC) system, the level of institutional excellence, and the role of organizational commitment as a mediating variable in the relationship between them, from the perspective of secondary school teachers in the Gaza Strip. The researchers employed the descriptive, analytical, and correlational approach and used a questionnaire consisting of 54 items distributed across three domains, applied to a sample of 358 secondary school teachers in the Gaza governorates. The results indicated that the degree of BSC implementation, as perceived by the sample, had a mean score of 3.76 out of 5, followed by institutional excellence (3.74), and then organizational commitment (3.68), all of which were rated as high. The findings also showed a statistically significant impact of the BSC on institutional excellence (61.5%) and on organizational commitment (43.7%). Furthermore, organizational commitment had a significant effect on institutional excellence (45.3%), and it was confirmed that organizational commitment functions as a mediating variable in this relationship. Based on the results, the researchers recommended strengthening training programs to enhance understanding and application of the Balanced Scorecard approach in performance evaluation and decision-making to keep pace with global changes, developing performance measurement frameworks, and promoting institutional excellence strategies by utilizing the study results, in addition to proposing future studies to explore the impact of BSC implementation in different educational sectors.
Keywords: Balanced Scorecard; mediator variable; institutional excellence; Organizational commitment impact; secondary schools in Gaza